Do Family-Owned Firms Behave More Responsibly? Examining the Effect of CSR on Tax Avoidance - Aljufri, Aljufri; Anita, Rizqa; Pardede, Niken; Abdillah, Muhammad Rasyid; Zakaria, Nor Balkish (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study examines the relationship between corporate social responsibility (CSR) and tax avoidance, and assesses how family ownership moderates this relationship within an agency theory perspective. The population consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022, with samples selected using a purposive sampling technique. Using regression analysis on 98 non-financial family firms (392 firm-year observations), the study finds that higher CSR engagement is associated with lower effective tax rates, indicating greater tax avoidance and challenging the conventional view of CSR as a disciplining mechanism. Although family ownership is positively related to tax compliance, its interaction with CSR increases tax avoidance. These findings suggest that family firms may use CSR instrumentally to enhance legitimacy, highlighting that CSRs ability to curb tax avoidance is context-dependent and shaped by governance dynamics.